Temperature profile and gas emissions of jet fuel using a low power flameless combustor - Barbosa, Jean Andrade; de Andrade, José Carlos; de Souza Costa, Fernando; Coronado, Christian Jeremi Rodriguez; de Azevedo, Cláudia Gonçalves [UNESP]; de Andrade, Ricardo Amaral (Springer Nature, 2022)
Flameless combustion has significant potential for aeronautical applications since it is a regime with homogeneous temperature distribution, relatively low temperatures, high thermal efficiency, reduced NOx emissions, and reduced thermal stress in the chamber. This work demonstrates the possibility of achieving flameless combustion of Jet A-1 fuel and presents experimental data obtained in a small combustion chamber that uses the energy generated to heat up the combustion air with a thermal input of 4.36 kW. A blurry injector was adopted for efficient fuel atomization (Sauter mean diameter of 28.6 ± 0.28 μ m) adjacent to the nozzle orifice exit. The evolution of the main process parameters has indicated transition from conventional combustion to flameless regime after 60 min from ignition, with excess combustion air of 70%, fuel mass flow rate of 0.1018 g/s and combustion air temperature 589 K. Combustion air momentum rate and velocity were 0.1678 N and 345 m/s, respectively, whereas the droplet vaporization time was estimated as 0.27 ms and residence time of 3.37 ms. Temperatures measured at different locations inside the chamber were within 987 ± 29.5 K after 75 min from ignition, and average NOx, UHC emissions were, respectively, 21.5 ppm and 1 ppm between 70 and 100 min from ignition and an increase of 20 ppm for CO emission.
Keywords: Combustion; Flameless; Flow blurry; Jet fuel; Thermodynamics